Comparison of Transforming Growth Factor-Beta 1 Concentration in Preeclampsia and Normal Pregnancy Women - Yusrawati Yusrawati; Dyka Aidina; Eti Yerizel (The Indonesian Biomedical Journal, 2017)
BACKGROUND: According to the theory of endothelial dysfunction, the pathogenesis of preeclampsia is associated with the imbalance of angiogenic and anti-angiogenic factors. Transforming growth factor-beta 1 (TGF-β1) has also proposed as a proangiogenic factor that influences preeclampsia. This study was conducted to compare a mean difference of TGF-β1 between preeclampsia and normal pregnancy.METHODS: This study was an observational crosssectional study with 25 subjects of pregnant women with preeclampsia and 25 subjects of normotensive pregnant women. The study was conducted in Dr. Reksodiwiryo Hospital, Bhayangkara Hospital, and Dr. Rasidin Hospital in Padang, Indonesia from October 2015 to January 2016. For the determination of TGF-β1 concentration, peripheral Abstract venous blood samples were taken. The blood samples were analyzed by enzyme-linked immunosorbent assay (ELISA) in Biomedical Laboratory, Faculty of Medicine, Andalas University. The mean difference was statically analyzed by independent samples T-test.RESULTS: The mean difference of TGF-β1 was lower in preeclampsia group than normal pregnancy group (2.02±0.99 ng/mL vs. 3.24±2.67 ng/mL; p<0.05).CONCLUSION: The TGF-β1 concentration was lower in pregnant women with preeclampsia. Thus, it may have a role as a marker in preeclampsia.KEYWORDS: preeclampsia, normal pregnancy, transforming growth factor-beta1, TGF-β1